Penerapan Insentif Pajak Dan Prinsip Akuntansi Konservatif Terhadap Manajemen Laba Pada Era Pandemi Covid-19 - Pradnyani, Ni Luh Putu Normadewi Abdi; Pramitari, I Gusti Ayu Astri; Nurhayanti, Ni Ketut (E-Jurnal Akuntansi, 2022)
The purpose of this study is to prove that the application of tax incentives and the principle of conservatism to financial statements has an effect on earnings management. The research was conducted on companies in the consignment goods industry sector on the IDX in 2019-2020. The research sample was taken using purposive sampling, in order to obtain as many as 15 companies that meet the criteria. The analytical tool used in this study is multiple linear regression using the IBM SPSS 25 software. The results show that earnings management practices during the COVID-19 pandemic are significantly affected by the application of tax incentives and accounting conservatism principles. The implications of the research can be taken into consideration for companies in making decisions. Keywords: Tax Incentives; Accounting Conservatism Principles; Earnings Management.